Desorption Behaviors and Adsorption Behaviors after Desorption of Trivalent Metal Ions Adsorbed on Chelating Resin: Comparison between Scandium(III) and Other Metal Ions - Hiroto WATANABE; Satoshi ASANO; Kuniaki MURASE (Journal of MMIJ, 2024)
Scandium (Sc) generally lacks independent deposits and is mainly recovered as a by-product of the smelting of other ores. Scandium is present in laterite ores in concentrations ranging from tens to hundreds of ppm. In the process of recovering nickel from laterite ores, Sc is recovered from sulfuric acid leachates. An ion-exchange resin method is an effective way to recover low concentrations of Sc (III) in sulfuric acid leachates. In our previous studies, the adsorption behaviors of Sc (III) and other trivalent metal ions were investigated, but the desorption behaviors of them were not. This study proposes optimal adsorption and desorption conditions for the selective separation and recovery of Sc from other trivalent cations in sulfuric acid solutions using an iminodiacetic acid chelating resin, Diaion™ CR11. The chelating resin with each metal ion adsorbed was mixed with sulfuric acid solution, and the desorption behaviors of these ions were investigated. On the other hand, adsorption tests were conducted using the chelating resin with residual Cr (III). The order of ease of desorption was Al (III) > Sc (III) > Fe (III) >> Cr (III). The desorption reaction rate of Cr (III) increased with increasing temperature, and its activation energy was estimated to be 82 - 93 kJ mol-1. Although the adsorption reaction rate and the amount of Sc (III) decreased with increasing residual amount of Cr (III) on the chelating resin, the adsorption ratio of Sc (III) was over 90% at a bed volume of 30 in a column test at 23˚C using the chelating resin with a residual amount of Cr (III) of 0.2 mmol g-1. With appropriate adsorption and desorption operations, scandium in laterite ores can be recovered continuously and efficiently, contributing to the development of the industry.